Signal-Centric Framework Based on Probability of Detection for Real-Time Reliability of Concrete Damage Inspection - Sena Tayfur (Applied Sciences)
Passive nondestructive testing (NDT) methods allow one to detect damage by the energies emitted from the internal processes. While the test conditions can be controlled and repeatable, obtained data are random, and the probability of detection (PoD) is affected. However, in concrete with complex fracture behavior, factors such as signal attenuation, sensor-damage distance, and test configuration influence the reliability of the test. The conventional practice of proceeding without assessing credibility prevents the ability to determine whether a configuration modification is required, necessitating reassessment. The main objective of this study is to develop a signal-centric framework to enhance the real-time reliability of inspection by investigating the PoD of acoustic emission (AE), a widely used passive NDT method for the real-time monitoring of structures. This study’s purpose is to evaluate the mechanical processes and the passive signal responses, emphasizing the detectability of cracking in concrete with two PoD approaches, namely, amplitude- and energy-based PoDs. Additionally, critical signal signatures, namely, signal-to-noise ratio (SNR) and frequency, were pinpointed for their direct influence on the detectability of the crack. With the outcomes obtained, a novel framework, which aims to provide an adaptive evaluation of the PoD of the technique, was suggested to achieve the desired quality in the damage detection of structures.